The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1250/ast.26.440
|View full text |Cite
|
Sign up to set email alerts
|

Statistical distribution of normal hearing thresholds under free-field listening conditions

Abstract: The statistical distribution of normal hearing thresholds for pure tones of frontal incidence under binaural, free-field listening conditions was estimated as a function of frequency. First, the form of threshold distribution was investigated with threshold measurement data of the present study and those of other studies. Analytical results indicate that the threshold distribution has a form of normal distribution for the frequency range from 25 Hz to 16 kHz. Second, under the assumption of normality, standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…This figure plots the skewness that the authors derived from two sets of threshold data for 89 individuals [4,19]. It is observed that the skewness deviates from zero at frequencies of 10,000 Hz and above.…”
Section: Measurement Conditions Of Hearing Thresholdmentioning
confidence: 99%
See 4 more Smart Citations
“…This figure plots the skewness that the authors derived from two sets of threshold data for 89 individuals [4,19]. It is observed that the skewness deviates from zero at frequencies of 10,000 Hz and above.…”
Section: Measurement Conditions Of Hearing Thresholdmentioning
confidence: 99%
“…Form of Hearing Threshold Distribution 2.3.1. At frequencies lower than 10,000 Hz [4] Statistical processing of the data and description of the results become easier if the dispersion of individual data can be approximated using a normal distribution (see Sect. 2.4).…”
Section: Measurement Conditions Of Hearing Thresholdmentioning
confidence: 99%
See 3 more Smart Citations